Diffuse Lung Diseases in Cigarette Smokers - Vassallo, Robert (Seminars in Respiratory and Critical Care Medicine, 2012)
Cigarette smoking is a recognized causative agent or precipitant of specific diffuse lung diseases characterized by bronchiolar and interstitial lung inflammation. Respiratory bronchiolitis-associated interstitial lung disease and pulmonary Langerhans cell histiocytosis are now considered smoking-induced diffuse lung diseases. Desquamative interstitial pneumonia is also recognized as a smoking-induced interstitial pneumonia in most cases. These disorders affect relatively young adult smokers and may be progressive. Although distinguishable by histopathological and radiographic features, significant overlap occurs in many cases with chest radiography and lung histology showing overlapping features of smoking-related bronchiolar and interstitial lung injury. Cigarette smoking is also recognized as an important precipitant of many acute eosinophilic pneumonia cases. Smokers are at higher risk of developing fibrotic interstitial lung diseases such as idiopathic pulmonary fibrosis and rheumatoid arthritis–associated interstitial lung disease. Certain smokers also develop combined emphysema and lung fibrosis. The avoidance of primary and second-hand cigarette smoke is a critical component of management for patients afflicted with these smoking-induced diffuse lung diseases. The role of corticosteroids and other immunosuppressive treatments in the management of smoking-related interstitial lung diseases remains poorly defined and should be reserved for individuals with progressive disease despite smoking cessation. Understanding mechanisms by which tobacco induces diffuse lung pathology is critical in the pursuit of novel therapeutic approaches for these diseases.
Keywords: respiratory bronchiolitis; desquamative interstitial pneumonia; interstitial lung disease; smoking; pulmonary Langerhans cell histiocytosis; acute eosinophilic pneumonia.